Myeloid-Derived Suppressor Cells Specifically Suppress IFN-γ Production and Antitumor Cytotoxic Activity of Vδ2 T Cells - Sacchi, Alessandra; Tumino, Nicola; Sabatini, Andrea; Cimini, Eleonora; Casetti, Rita; Bordoni, Veronica; Grassi, Germana; Agrati, Chiara (Frontiers in Immunology, 2018)
γδ T cells represent less than 5% of circulating T cells, they exert a potent cytotoxic function against tumor or infected cells, and secrete cytokines like conventional αβ T cells. As αβ T-cells γδ T cells reside in the typical T cell compartments (the lymph nodes, and spleen), but are more widely distributed in tissues throughout the body. For these reasons, some investigators are exploring the possibility of immunotherapies aimed to expand and activate Vδ2 T cells, or using them as CAR carriers. However, the role of immunosuppressive microenvironment on Vδ2 T cells during infections and cancers has not been completely elucidated. In particular, the effects of myeloid derived suppressor cells (MDSC), largely expanded in such pathologies, was not explored. In the present work we demonstrated that MDSC may inhibit IFN-γ production and degranulation of phosphoantigen-activated Vδ2 T cells. Moreover, the Vδ2 T cells cytotoxic activity against the burkitt lymphoma cell line Daudi and Jurkat cell line were impaired by MDSC. The ArgI seems to be involved in the impairment of Vδ2 T cell function induced by both tumor cells and MDSC. These data open a key issue in the context of Vδ2-targeted immunoteraphy, suggesting the need of combined strategies aimed to boost Vδ2 T cells circumventing tumor- and MDSC-induced Vδ2 T cells suppression.